- #1

- 205

- 0

f(x)=3x^2+6x+7 on [-2,3]

so f(3)-f(-2)=f'(x)(3+2)

i get 52-7=(6x+6)(5)

then 45=30x+30

then 5=30x

and x=1/6

where am i going wrong?

- Thread starter Rasine
- Start date

- #1

- 205

- 0

f(x)=3x^2+6x+7 on [-2,3]

so f(3)-f(-2)=f'(x)(3+2)

i get 52-7=(6x+6)(5)

then 45=30x+30

then 5=30x

and x=1/6

where am i going wrong?

- #2

Dick

Science Advisor

Homework Helper

- 26,260

- 619

You seem to have computed 45-30=5?!

- #3

- 205

- 0

oohhh my! thank you so much! i didnt see that !

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 3

- Views
- 703

- Last Post

- Replies
- 5

- Views
- 2K

- Last Post

- Replies
- 6

- Views
- 1K

- Last Post

- Replies
- 7

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 1K

- Last Post

- Replies
- 18

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 4

- Views
- 791

- Last Post

- Replies
- 2

- Views
- 1K